Case Report: Response to Almonertinib in a Patient With Metastatic NSCLC Resistant to Osimertinib due to Acquired EGFR L718Q Mutation - Shen, Gang; Shi, Lei; Tian, Xin; Huang, Depei; Chen, Hao; Gao, Chan; Shen, Xudong; Zhang, Hushan (Frontiers in Pharmacology, 2021)
Osimertinib shows strong clinical activity in first- and second-line treatment of nonsmall-cell lung cancer (NSCLC) patients with epidermal growth factor receptor (EGFR) mutations, especially EGFR T790M. However, when patients develop resistance, there is currently no definite postosimertinib treatment option. Herein, we report a patient with metastatic NSCLC who benefited from almonertinib after developing resistance to osimertinib.